2012
DOI: 10.4319/lom.2012.10.666
|View full text |Cite
|
Sign up to set email alerts
|

An improved energy‐dispersive X‐ray microanalysis method for analyzing simultaneously carbon, nitrogen, oxygen, phosphorus, sulfur, and other cation and anion concentrations in single natural marine microplankton cells

Abstract: Electron‐probe X‐ray microanalysis (XRMA) is a technique that can be used to simultaneously quantify C, N, O, Na, Mg, Al, Si, P, S, Cl, K, and Ca present in single cells collected from the sea, with a minimal treatment of the samples. The technique has been used to determine elemental composition in plankton using scanning electron microscopes (SEM) or transmission electron microscopes (TEM). The methodologies used have shown some drawbacks. Here we present an improved methodology focusing on the analysis of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…Unfortunately, data on the elemental composition of plankton in nature is still too sparse to validate these hypotheses [ 9 , 12 ], specially for particulate phosphorus [ 13 ]. Two relatively new methods, energy dispersive X-ray microanalysis (XRMA, also abbreviated as EDX or EDS for energy dispersive X-ray spectroscopy) [ 14 , 15 ] and synchrotron–based X-ray fluorescence microprobe (SXRF) [ 16 ], show promise to overcome this scarcity. However, these methods are not yet routinely applied and the existing data is still limited, available only for a few taxonomic groups and environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, data on the elemental composition of plankton in nature is still too sparse to validate these hypotheses [ 9 , 12 ], specially for particulate phosphorus [ 13 ]. Two relatively new methods, energy dispersive X-ray microanalysis (XRMA, also abbreviated as EDX or EDS for energy dispersive X-ray spectroscopy) [ 14 , 15 ] and synchrotron–based X-ray fluorescence microprobe (SXRF) [ 16 ], show promise to overcome this scarcity. However, these methods are not yet routinely applied and the existing data is still limited, available only for a few taxonomic groups and environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, the biota and its elemental composition are related to the hydrogeochemistry of water. For example, in diatoms and marine dinoflagellates, the presence of Ca, K, Mg, P, S and Si has been reported as part of the composition of their body structure (Segura-Noguera et al, 2012). Also, variations in the concentrations of Ca, Cl, K, Na, Mg, P, S and Si in Ceratium hirundinella are caused by seasonality (Sigee et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The X-ray penetration range of 1,000 nm. The average penetration range in X-ray analyses is 2.275 µm (Segura-Noguera et al, 2012). INCA suite 3.04 was used for the quantitative analyses (the total composition percent of the detected elements).…”
Section: Micro and Macroelement Analysis By Scanning Electron Microscmentioning
confidence: 99%
“…However, these studies commonly reported averaged trait values and did not present the distribution of these stoichiometric traits. Since these early studies, the equipment and techniques used for EDS have improved and enabled single-cell stoichiometries to be detected and reported with greater sensitivity and in higher resolution (Segura-Noguera et al, 2012;Watanabe, 2013). Here, we aim to advance the description of the stoichiometric trait distribution for cultured and uncultured bacteria by integrating single cell EDS-generated stoichiometric data into probability density functions to describe the frequency distribution of stoichiometric traits of individual bacterial cells within a population or community.…”
Section: Introductionmentioning
confidence: 99%